Peruvian college students’ knowledge on dental veneers - Dávila-Ventura, Stephany; Roncal-Espinoza, Rosa Josefina (Revista Facultad de Odontología Universidad de Antioquia, 2023)
Introduction: dental veneers are an aesthetic treatment option requested mostly to improve appearance. In Peru, there are few investigations that measure knowledge about this treatment. Therefore, the objective of this study was to determine the knowledge about dental veneers in students at a Peruvian university. Methods: descriptive, prospective, and cross-sectional study; made up of a population of 1417 students enrolled during the year 2022 in the Schools of Human Medicine, Psychology and Nursing of the Santo Toribio de Mogrovejo Catholic University, from which a sample size of 160 participants was obtained; however, there were 187 who answered the questionnaire. The instrument was previously validated through expert judgment and, through the Kuder Richardson test, a high reliability corresponding to 0.7 was obtained. Data analysis was performed using descriptive statistics and Pearson's Chi-square test. Results: the participants were 55 men and 132 women. A medium level of knowledge about the treatment with dental veneers was reported in 75,9% of the students, and a low level in 5,9% of them. The population mostly obtained information from more than one source, followed by social networks, friends and / or relatives, television programs and, finally, by the dentist. Conclusion: knowledge about dental veneers in students from a Peruvian university was medium level, these results were similar when evaluated between sex, age, professional school, and source of information.